Change in the expression of receptors to wheat germ lectin (WGA) on epithelioreticulocytes in the thymus of rats under normal conditions and after prenatal dexamethasone administration - Aravitskiy, E. O.; Аравіцький, Євген Олегович (My University, 2025)
Aim: To study the dynamics of wheat germ lectin (WGA) receptor expression on rat thymic epithelial cells in normal conditions and after prenatal administration of dexamethasone.